Single monopoly profits, vertical mergers, and downstream entry deterrence - Matthias Hunold; Jannika Schad (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2021)
We review the Chicago school's single monopoly profit theory whereby an upstream monopolist cannot increase its profits through vertical integration as it has sufficient market power anyways. In our model the dominant supplier has full bargaining power and uses observable two-part tariffs. We show that, by vertically integrating with a downstream incumbent, the supplier can profitably commit to pricing more aggressively if a downstream entrant refuses its supply contract. This can deter welfare-enhancing entry. The anti-competitive effects arise from the seemingly pro-competitive elimination of double marginalization. We relate our model to hybrid platforms and, in particular, Apple's App store.
Keywords: L22; L40; L42; 330; double marginalization; entry deterrence; exclusive dealing; foreclosure; verticalmerger